OER-BASED E-LEARNING INITIATIVES IN DISTANCE LEARNING: A CASE STUDY OF WAWASAN OPEN UNIVERSITY - Jasmine Selvarani Emmanuel, Mohandas, Balakrishna Menon, Vighnarajah, (PJDOL, 2023)
Wawasan Open University (WOU) established in 2007 has been adopting the latest applications in e-learning along with the principles and practices of open education movement. This paper reports the development of OER-based e-learning in the University since 2011 after the commencement of the OER-Asia initiative and the formulation of anOER Policy and adoption of the Open License Policy